Legal regulation of certain types of unnamed contracts - Tatar, Olga (Editura USM, 2024)
To date, the topic dedicated to the institution of an unnamed contract in the civil law of the Republic of Moldova is relevant, however, due to little study, it remains open for comprehensive legal research. Whenever a question arises regarding the criteria for non-named contracts, the application of imperative and dispositive norms to them, the definition of the boundaries of freedom to conclude such contracts, the legislator faces difficulties, both at the level of doctrine and at the level of practice. The regulation of civil relations is possible not only through their consolidation in the normative order, but also through the individual consolidation of the contract between certain subjects, in a certain order and on certain conditions, since the subjects of civil circulation, guided by the principle of freedom of contract, They are free to conclude both stipulated and nonstatutory contracts. Such contracts are called nameless, atypical, unnamed, unnamed contracts. The conclusion of independent unnamed contracts is due to the fact that the subjects of civil legal relations have new needs associated with the growth of scientific and technological progress, the improvement of information networks in a competitive environment. The reason for all this was the evolution of the economic life of the Republic of Moldova and its transition from administrative methods of managing the economy to the principles of a market economy, which entailed the entire civil turnover and, subsequently, the modern contractual forms that arose.

Până în prezent, tema dedicată instituirii unui contract nenumit în dreptul civil al Republicii Moldova este relevantă, totuși, din cauza puținului studiu, rămâne deschisă cercetării juridice cuprinzătoare. Ori de câte ori apare o întrebare privind criteriile pentru contractele nenumite, aplicarea normelor imperative și dispozitive acestora, definirea limitelor libertății de a încheia astfel de contracte, legiuitorul se confruntă cu dificultăți, atât la nivel de doctrină, cât și la nivel. de practică. Reglementarea raporturilor civile este posibilă nu numai prin consolidarea lor în ordinea normativă, ci și prin consolidarea individuală a contractului dintre anumiți subiecți, într-o anumită ordine și în anumite condiții, întrucât subiecții circulației civile, ghidați de principiul de libertate contractuala, Sunt liberi sa incheie atat contracte stipulate cat si contracte nestatutare. Astfel de contracte se numesc contracte fără nume, atipice, fără nume, fără nume. Încheierea de contracte independente fără nume se datorează faptului că subiecții 86 raporturilor juridice civile au noi nevoi asociate cu creșterea progresului științific și tehnologic, îmbunătățirea rețelelor informaționale într-un mediu concurențial. Motivul pentru toate acestea a fost evoluția vieții economice a Republicii Moldova și trecerea acesteia de la metodele administrative de conducere a economiei la principiile unei economii de piață, care a presupus întreaga cifră de afaceri civilă și, ulterior, formele contractuale moderne care apărea.
REGLEMENTAREA LEGALĂ A UNOR TIPURI DE CONTRACTE NENUMITE
Keywords: subjects of a civil contract; unnamed contracts; principle of freedom of contract; institutions of law; subiecții unui contract civil; contracte nenumite; principiul libertății contractuale; instituții de drept